Date Palm (Phoenix dactylifera L.) Flour as an Alternative Culture Media for the Growth of Escherichia coli and Bacillus cereus - Chylen Setiyo Rini; Ida Agustini Saidi; Jamilatur Rohmah (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2023)
The high cost of bacterial growth culture media can result in obstacles in the process of practicum or research in the field of microbiology. Date palm (Phoenix dactylifera L.) is the oldest fruit plant that grows in the Arabian Peninsula, North Africa and the Middle East. Dates are a source of high energy food with sugar content of 72% - 88%. This research was conducted to test the ability of date palm flour to grow Escherichia coli and Bacillus cereus bacteria as an alternative medium to replace NA media. In this study using total number of bacteria/ TPC (Total Plate Count) method to calculated the number of colonies of bacteria. The results of this study the number of colonies of Escherichia coli bacteria was more than the number of colonies of Bacillus cereus, that is 54 x 105CFU/g on concentration media 8 gr. When compared with NA media, date palm flour media can be used as an inexpensive alternative culture medium for bacteria.